Ethnobotanical survey of the main medicinal plants used in the city of Piripiri-PI, with the objective of implementing an herbal pharmacy (Research, Society and Development, 2022)
It is known since the first civilizations the beneficial effects that nature offers, with high diversity, knowledge and techniques that have been improved and passed on over several generations to the present days. This article aims to obtain data regarding the use of medicinal plants by the population of the city of Piripiri - Piauí for later construction of a medicinal plant garden contemplating the main species used by the local community. Data collection was carried out through interviews with the city population, the sample was calculated with a confidence level of 90 % and a sampling error of 10 % of the population of the mentioned city. Regarding the results, it is noticeable that most of the plants mentioned are part of the list of medicinal plants most used in the Northeast. The most cited plants by the community are: Mexican tea, Boldo and Lemon balm with 10 %, followed by Lemon grass and Basil with 9%. In these reported uses, the most treated illnesses were headache (33%), flu (23%), insomnia (21%), cold (14%), fever (4%) and reflux (5%). The researched population denotes the conception that, as natural products, they are free from harm to health. Guidance by health professionals is necessary to explain about its rational use. The present study stands out for being able to contribute to the literature with regard to promoting the use of medicinal plants by the population and highlighting this possibility of using the resources offered by nature for therapeutic purposes.